Film Flip and Transfer Process to Enhance Light Harvesting in Ultrathin Absorber Films on Specular Back‐Reflectors. Issue 35 (10th July 2018) - Kay, Asaf; Scherrer, Barbara; Piekner, Yifat; Malviya, Kirtiman Deo; Grave, Daniel A.; Dotan, Hen; Rothschild, Avner
Abstract: Optical interference is used to enhance light–matter interaction and harvest broadband light in ultrathin semiconductor absorber films on specular back‐reflectors. However, the high‐temperature processing in oxygen atmosphere required for oxide absorbers often degrades metallic back‐reflectors and their specular reflectance. In order to overcome this problem, a newly developed film flip and transfer process is presented that enables high‐temperature processing without degradation of the metallic back‐reflector and without the need of passivation interlayers. The film flip and transfer process improves the performance of photoanodes for photoelectrochemical water splitting comprising ultrathin (<20 nm) hematite (α‐Fe2 O3 ) films on silver–gold alloy (90 at% Ag–10 at% Au) back‐reflectors. Specular back‐reflectors are obtained with high reflectance below hematite films, which is necessary for maximizing the productive light absorption in the hematite film and minimizing nonproductive absorption in the back‐reflector. Furthermore, the film flip and transfer process opens up a new route to attach thin film stacks onto a wide range of substrates including flexible or temperature sensitive materials. Abstract : A film flip and transfer process is introduced to enable fabrication of nanophotonic structures that leverage a strong optical interference in ultrathin absorbers. This method enables high‐temperature processing of metal‐oxide absorbers without degradation of the metallic back‐reflector. It is showcased by fabricating highly absorbing hematite ultrathin films on specular silver–gold back‐reflectors for use in solar water splitting.